Assessing the cost‐effectiveness of RT Prepare: A radiation therapist–delivered intervention for reducing psychological distress prior to radiotherapy. Issue 5 (10th April 2019) - Youens, David; Halkett, Georgia; Wright, Cameron; O'Connor, Moira; Schofield, Penelope; Jefford, Michael; Aranda, Sanchia; Kane, Robert; Moorin, Rachael; ,
Abstract: Objective: To determine the cost‐effectiveness of RT Prepare in reducing breast cancer patients' psychological distress before treatment, compared with usual care. Methods: RT Prepare, an intervention involving patient education and support consultations with a radiation therapist (RT), was implemented at three Australian sites (Australian New Zealand Clinical Trials Registration: ACTRN12611001000998). The primary outcome was change in psychological distress using the Hospital Anxiety and Depression Scale (HADS); secondary outcomes were changes in quality of life (QoL) and additional health service use. Costs (2015 $AU) included consultation time and training delivery. Between‐group comparisons of HADS and QoL used generalised linear mixed models, and comparisons of health service use used negative binomial regression. Incremental cost‐effectiveness ratios (ICERs) indicated mean costs per 1‐point decrease in HADS score. Sensitivity analyses explored variation in facility size and uncertainty in intervention effectiveness. Results: Among 218 controls and 189 intervention participants, the intervention significantly lowered HADS scores at treatment commencement (adjusted mean difference 1.06 points). There was no significant effect on QoL or additional service use. Mean intervention costs were AU$171 per participant (US$130, €119) mostly related to RT training (approximately AU$142 (US$108, €99). An ICER of $158 (US$120, €110) was estimated. Cost‐effectiveness improved in a sensitivity analysis representing a large facility with higher patient numbers. Conclusion: This study provides new data on the cost‐effectiveness of an RT‐delivered intervention to reduce psychological distress prior to treatment, which will be useful to inform delivery of similar services. As most costs were upfront, cost‐effectiveness would likely improve if implemented as standard care.